O fungo Duddingtonia flagrans: controle biológico de nematodeos parasitas de bovinos à campo - Jobim, Marta Bañolas (2006)
The biological control is an alternative method to reduce the population of parasites by the use of natural antagonist. In the present study, the efficacy of nematophagous fungus Duddingtonia flagrans was tested to control gastrointestinal nematodes parasites of cattle livestock in the field. Twenty calves were used, distributed equally in two distinct plots formed for native pasture. . Group A was treated with D. flagrans fungus, cultivated in sorghum, in a concentration with 1x106 clamidospores/kg body weight, mixed with maintenance ration, each day, during eight months. Group B served as a control and did not receive the fungus. Samples for faecal egg count (FEC), were collected each week. There were monthly counts in faecal cultures to identify the species of nematodes larvae, weight of the animals, collection of blood to determine red cell counts and collection of pasture to the counting of larvae. Temperature and rainfall data were registered daily. The FEC reduced around 56,84% in the last 3 months of the experiment, with a variation between 40,44 and 67,14% in the treated group (P<0,001). The faecal cultures demonstrated that the main nematodes been found were Cooperia and Haemonchus in a percentage of 47,9 and 35,3%, respectively. The counting of larvae in the pasture showed a reduction percentage around 77,05% in the treated group at the end of experiment (P<0,01). It could be concluded with this study, that fungus Duddingtonia flagrans is, without a doubt important, mainly in the reduction of the FEC and the significant reduction of larvae in the pasture. Therefore, this nematophagous fungus is efficient as a biological tool to be used in an integrated control of nematodes of bovine raised in the fields.